From weight loss to cancer treatment: Fasting as an adjuvant anticancer therapy - Wamidh H. Talib; Aseel J. Ali; Media Mohammed Baban; Jehan Abdul Sattar Salman; Hadeel Shaher Al Junaidi; Layan Abdulrahem Jumah; Rana Hameed Radhi; Ruba Emad Fleifel; Sara Feras Abuarab; Arkan Hadi Al-Yasari; Rawan W. Hadi; Anfal Al-Dalaeen (Pensoft Publishers, 2024)
The number of studies that have been conducted on the possible benefits of different types of fasting or calorie restriction on cancer therapy, including the likelihood that these treatments lessen side effects, has been limited. However, the results are nevertheless promising. Chemotherapy's adverse effects have led to a quest for options that reduce reliance on it. The susceptibility of tumorous cells to specific metabolites and nutrient deficiency is increasingly recognized as a key characteristic of the disease. This review delves into the data on various fasting methods and calorie restriction in rodents and humans, with a focus on biological adaptations that could potentially lower cancer risk or enhance cancer treatment results. We also emphasize recent scientific developments regarding the use of prolonged fasting and fasting-mimicking diets as a possible additional treatment for patients receiving immunotherapy or other treatments. This approach shows promise in enhancing treatment effectiveness, preventing resistance, and minimizing side effects. This study proposes that combining fasting and calorie restriction with chemotherapy, immunotherapy, or other therapies might be a potential technique to improve treatment efficacy, avoid resistance, and reduce adverse effects.